(untitled) (Research, Society and Development, 2021)
Objective: to analyses scientific productions about integrality in the educative practices in the scholar context. Method: integrative review of the literature realized in the bases of data PUBMED, LILACS, BVS and SCIELO through of descriptors crossings: “intersectorial action” and “school health”. Seven publications were chosen, of these increase two thematic categories: skills to educative practices in the scholar scenery and challenges and limits of them. Results: The analyses of studies showed that actions executed by health professionals are traditional educative practices and introduced in the scholar enenvironment. These professionals have difficulties and fragilities in the formation to develop more dialogical and participative educative practices that get possibility to the process in the formation of reflexive and critical citizens in a perspective applied of health promotion. Conclusion: to raise to power educative processes remain what let the ability to professionals to exercise of educative practice based for integrality in the public politics.